(untitled) (Global Conference on Medical and Health Sciences, 2026)
Post-traumatic coxarthrosis represents one of the most clinically significant sequelae of hip joint injuries, accounting for approximately 12–18% of all coxarthrosis cases encountered in orthopaedic practice worldwide (Tannast et al., 2015; Ganz et al., 2008). Unlike primary osteoarthritis, which develops predominantly as a consequence of age-related cartilage degeneration, post-traumatic coxarthrosis arises following a spectrum of injuries including acetabular fractures, femoral head and neck fractures, hip dislocations, and traumatic labral tears. The structural alterations induced by such injuries disrupt the biomechanical equilibrium of the hip joint and initiate a cascade of morphological changes involving articular cartilage, subchondral bone, the joint capsule, and periarticular soft tissues (Marsh et al., 2010; Thomas et al., 2017). A detailed understanding of the morphological and morphometric characteristics of the hip joint in post-traumatic coxarthrosis is essential for surgical planning, particularly in the context of total hip arthroplasty (THA), which remains the definitive treatment for advanced-stage disease (Matta et al., 2012).